Ovarian response to superovulation in Nelore cows (Bostaurusindicus L.) - Becker, W. A P; Pinheiro, L. E L [UNESP] (Elsevier, 1986)
Superovulation was induced in 15 Nelore cows with porcine follicle stimulating hormone (FSH-P) or pregnant mare serum gonadotropin (PMSG), and embryos were collected to compare the response of this breed of cattle to these hormones. FSH-P was given in 30-and 40-mg doses for 5 d as a single daily injection or fractionated into two daily injections. PMSG was given in doses of 1000 and 2000 IU. The animals were killed immediately after embryo collection and the ovaries and genitalia were examined clinically. PMSG proved to be more effective in inducing superovulation than FSH-P, probably because PMSG caused no stress since it was administered as a single dose. No differences were observed between the 30-and 40-mg dose of FSH-P or between the application as a single or fractionated dose. Differences did occur, however, between the number of ovulations and embryos obtained at each collection. On the basis of postmortem analysis, we concluded that lack of egg uptake by the infundibulum had occurred in cases of increased ovulation, with excessive increase in volume of the ovary. We also recommend using smaller doses of FSH-P and suggest that avoiding stress in handling is essential for a good response to hormonal stimulation by Zebu cattle. © 1986.
Keywords: FSH-P; Nelore; PMSG; superovulation